Case Study of the Implementation of Drawing Therapy and Music Therapy in Reducing Hallucinations in the Grahanisadha Room of the Bali Provincial Mental Hospital - Ni Made Dian Sulistiowati; Cendani, Ni Ketut Ari (PT Saintek Medika Nusantara, 2025)
Hallucinations if left untreated can pose a risk of harm to yourself and others. The application of drawing therapy and music therapy can reduces hallucinatory symptoms in schizophrenic patients. The purpose of the study was to determine the results of the effect of drawing therapy and music therapy on hallucinations in schizophrenic patients. This research design is a case study of patients with hallucinations, qualitative research type. The sample of this study amounted by one respondent who experiences hallucinations, where drawing therapy is carried out 2-3 times a week while music therapy is carried out 5 times with a duration of 10-15 minutes per meeting. The results show that there is an effect of applying drawing art therapy and music therapy on reducing hallucinatory symptoms in hallucinatory patients. Drawing therapy and music therapy have several benefits such as providing motivation, entertainment and diversion of attention so that the patient's mind is not focused on hallucinations. They were considered to have an effect in reducing hallucinatory symptoms in patients with hallucinations.